Neurocognitive Change in the Era of HIV Combination Antiretroviral Therapy: The Longitudinal CHARTER Study. (31st October 2014) - Heaton, Robert K.; Franklin, Donald R.; Deutsch, Reena; Letendre, Scott; Ellis, Ronald J.; Casaletto, Kaitlin; Marquine, Maria J.; Woods, Steven P.; Vaida, Florin; Atkinson, J. Hampton; Marcotte, Thomas D.; McCutchan, J. Allen; et al.
Abstract : CNS HIVAnti-Retroviral Therapy Effects Research examined incidence and predictors of neurocognitive (NC) change in 436 human immunodeficiency virus (HIV)-infected adults over 4–7 semiannual visits; 22.7% evidenced NC decline and 16.5% NC improvement. These changes were predicted by HIV disease and treatment factors, demographics, and comorbid conditions. Abstract: Background.  Human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) can show variable clinical trajectories. Previous longitudinal studies of HAND typically have been brief, did not use adequate normative standards, or were conducted in the context of a clinical trial, thereby limiting our understanding of incident neurocognitive (NC) decline and recovery. Methods.  We investigated the incidence and predictors of NC change over 16–72 (mean, 35) months in 436 HIV-infected participants in the CNS HIV Anti-Retroviral Therapy Effects Research cohort. Comprehensive laboratory, neuromedical, and NC assessments were obtained every 6 months. Published, regression-based norms for NC change were used to generate overall change status (decline vs stable vs improved) at each study visit. Survival analysis was used to examine the predictors of time to NC change. Results.  Ninety-nine participants (22.7%) declined, 265 (60.8%) remained stable, and 72 (16.5%) improved. In multivariable analyses, predictors of NC improvements or declines included time-dependent treatment status and indicators of disease severity (current hematocrit, albumin, total protein, aspartate aminotransferase), and baseline demographics and estimated premorbid intelligence quotient, non-HIV-related comorbidities, current depressive symptoms, and lifetime psychiatric diagnoses (overall model P < .0001). Conclusions.  NC change is common in HIV infection and appears to be driven by a complex set of risk factors involving HIV disease, its treatment, and comorbid conditions.